Audio-Lingual Method To Improve Students’s Speaking Skill At SMP Negeri 1 Baranti - Hardiyanti Rahman; Suhartini Khalik; Sam hermansyah; Geminastiti Sakkir (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2021)
The objective of this research was to find out whether or not the use of the Audio-Lingual method to improve students’ speaking skill at the eighth-grade SMP Negeri 1 Baranti.This research used the experimental method. The population of this study was one class of class VIII.1 of SMP Negeri 1 Baranti were 23 students. The sample of this study was 23 students. This sample was taken using the cluster random sampling technique. This research applied the audio-lingual method in the class. This research applied one type of speaking skill testing to determine students' speaking skill.The researcher found that the use of the audio-lingual method in teaching speaking, it could improve the speaking skill of the grade VIII.1 students of SMP Negeri 1 Baranti. The mean score of pre-test (54,30) was lower than mean score of post-test (57,04), showed that the p-value was lower than the α (0,000 < 0,05) on the significant level (α=0,05). So, the researcher stated that H0 was rejected and H1 was accepted. Based on data analysis, the researcher concluded that audio-lingual method was effective in improving students speaking skill of class VIII.1 of SMP Negeri 1 Baranti